2009
DOI: 10.1016/j.apor.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced predictions of wave impact pressure by improved incompressible SPH methods

Abstract: a b s t r a c tA new criterion is proposed for a more efficient assessment of free-surface particles in a particlebased simulation. Enhanced wave impact simulations are carried out by improved Incompressible SPH (ISPH) methods. The first improvement is the same as that in the Corrected ISPH (CISPH; [Khayyer A, Gotoh, H, Shao SD. Corrected incompressible SPH method for accurate water-surface tracking in breaking waves, Coast Eng 2008; 55 (3): 236-250]) method and is proposed for the improvement of momentum cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(66 citation statements)
references
References 30 publications
1
65
0
Order By: Relevance
“…In addition, attempts are also made by improving the source term. Khayyer et al (2009) replaced the source term by a higher-order source term, while Kondo and Koshizuka (2011), Khayyer and Gotoh (2011), Khayyer and Gotoh (2013), Gotoh and Khayyer (2016) and Gotoh et al (2014) introduced an error-compensating term (including a highorder main term and two error-mitigating terms multiplied by dynamic coefficients). The higher-order source and the error-compensating terms help to enhance the pressure field calculation, volume conservation and uniform particle distributions throughout the simulation that minimizes the perturbations in particle motions.…”
Section: Mathematical Formulation Of Projection-based Meshless Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, attempts are also made by improving the source term. Khayyer et al (2009) replaced the source term by a higher-order source term, while Kondo and Koshizuka (2011), Khayyer and Gotoh (2011), Khayyer and Gotoh (2013), Gotoh and Khayyer (2016) and Gotoh et al (2014) introduced an error-compensating term (including a highorder main term and two error-mitigating terms multiplied by dynamic coefficients). The higher-order source and the error-compensating terms help to enhance the pressure field calculation, volume conservation and uniform particle distributions throughout the simulation that minimizes the perturbations in particle motions.…”
Section: Mathematical Formulation Of Projection-based Meshless Methodsmentioning
confidence: 99%
“…There are several approaches for doing so, such as detecting if the density (particle number density) is smaller than a specified value (e.g. Lo and Shao 2002;Gotoh and Sakai 2006), mixed particle number density and auxiliary function method (Ma and Zhou 2009) and an auxiliary condition proposed by Khayyer et al (2009). For implementing in/outlet conditions and other more details about the treatment of boundary conditions, the readers are referred to the recent review papers by Violeau and Rogers (2016) and Gotoh and Khayyer (2016).…”
Section: Mathematical Formulation Of Projection-based Meshless Methodsmentioning
confidence: 99%
“…By using both the density criterion (Shao and Lo, 2003) and above symmetry criterion, the misjudgment of particles near the free surface or solid corner can be avoided. It is worth to mention that similar symmetry criterion has also been used by Khayyer et al (2009) but in a slightly simpler formulation.…”
Section: Free Surface Trackingmentioning
confidence: 99%
“…G贸mez-Gesteira et al [23], Shao [24], and Cleary and Rudman [25] employed the incompressible SPH method for determining both oceanic and offshore hydrodynamics. The incompressible SPH model has recently been applied to simulate the industrial and environmental flows associated with incompressible free-surface fluids [26][27][28][29][30][31][32][33]. It was also used to simulate the highly nonlinear two-dimensional sloshing phenomenon, as in the studies of Souto-Iglesias et al [34], Rafiee et al [35], Marsh et al [36], and Shao et al [37].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that problems encountered in weakly compressible SPH when solving incompressible flows could be resolved by using an incompressible SPH scheme. Khayyer et al [28,29] also proposed a corrected incompressible SPH method, which was developed, based on a variational approach to ensure the angular momentum conservation of incompressible SPH formulations. Recently, a stabilized incompressible SPH method involving relaxation of the density invariance condition was proposed by Asai et al [31].…”
Section: Introductionmentioning
confidence: 99%